2011
DOI: 10.1108/03321641111133154
|View full text |Cite
|
Sign up to set email alerts
|

Domains of validity of quasistatic and quasistationary field approximations

Abstract: Purpose -The paper aims at proposing a uniform and demonstrative description of two well-known and widely used approximations of slowly time-varying electromagnetic fields, i.e. the electro-quasistatic and the magneto-quasistationary approximation to Maxwell's equations. Design/methodology/approach -Under both approximations, the orders of magnitude of the relative errors of the dominant fields are analyzed by using three characteristic time constants. These time constants are determined by considering the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…[t can be easily shown that the two scalings (1) and (2) obtained here by dimensional analysis are in agreement with those expressed in terms of fields and time scalings given in [5]. Note howe ver that the existence of two Galilean limits is not so obvious if we naively take the limit c ----+ +00 in equations (6) and (7) (see [1] for the details).…”
Section: Introductionsupporting
confidence: 74%
“…[t can be easily shown that the two scalings (1) and (2) obtained here by dimensional analysis are in agreement with those expressed in terms of fields and time scalings given in [5]. Note howe ver that the existence of two Galilean limits is not so obvious if we naively take the limit c ----+ +00 in equations (6) and (7) (see [1] for the details).…”
Section: Introductionsupporting
confidence: 74%
“…Therefore, unlike in the magnetoquasistatic case, charge conservation is maintained [11]. Limits for the validity of the electroquasistatic approximation in terms of values of the electric permittivity as well as the electric conductivity based on characteristic time constants are also derived in [7], [9], [8]. Again, these limits are more strict than the quasi-stationary condition (1), as, starting from the Darwin model, a further reduction in the level of mutual coupling between the separate equations is carried out.…”
Section: The Electroquasistatic Modelmentioning
confidence: 99%
“…As it constitutes a further simplification based on the Darwin model, the range of validity of this approximation is restricted to a smaller spectrum of practical problems regarding the allowed rate of change of the electromagnetic fields. Estimations based on characteristic time constants are provided in [7], [9], [8]. Note that resonance cannot be observed within this model as no electric but rather magnetic energy is stored in the fields.…”
Section: B the Magnetoquasistatic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] If radiation as well as propagation effects are a-priori known to be negligible for a specific problem under consideration, alternative mathematical descriptions of electromagnetic phenomena can be found. The prerequisite mentioned above can be expressed based on the diameter d of the sphere containing the geometrical structure of interest and the minimum expected cycle time t of the electromagnetic waves as shown by Haus and Melcher [1989] and Steinmetz et al [2009]. When…”
Section: Quasistationary Approximationmentioning
confidence: 99%